A Case Report of Partial Hanging (Indian Internet Journal of Forensic Medicine and Toxicology, 2011)
Hanging is the form of asphyxia due to constriction of neck when the force of constriction is on the body weight. Hanging is commonly suicidal in nature. While, partial hanging is usually taken to be diagnostic of being suicidal in nature. The authors describe here a typical case of partial suicidal hanging.
Keywords: Hanging; Partial hanging; Ligature mark; Saliva stain.